A new point-of-care portable immunosensor for non-invasive assessment of oro-ileal transit time by oral fluid tauroursodeoxycholate measurement after its oral load - Simoni, Patrizia; Magliulo, Maria; Mirasoli, Mara; Vestito, Amanda; Festi, Davide; Roda, Giulia; Colecchia, Antonio; Roda, Aldo (Journal of pharmaceutical and biomedical analysis, 2013)
•Oro-ileal transit time was assessed by TUDCA salivary profile after its oral load.•A portable chemiluminescence immunosensor was developed to measure salivary TUDCA.•The developed immunosensor allows for accurate oro-ileal transit time determination.•An increased oro-ileal transit time was detected after treatment with Loperamide.•Oro-ileal transit time has been non-invasively evaluated in a point-of-care setting. A non-invasive test for oro-ileal transit time (OITT) evaluation was developed, based on the measurement of tauroursodeoxycholic acid (TUDCA) oral fluid concentration profile after its oral administration. Exploiting the fact that TUDCA is actively absorbed only in the ileum, OITT is measured as the time corresponding to TUDCA maximum oral fluid concentration (tmax). To measure oral fluid TUDCA concentration in a point-of-care setting, an ultrasensitive portable immunosensor was developed, based on a competitive chemiluminescent enzyme immunoassay (CL-EIA), using immobilized anti-TUDCA antibody and an ursodeoxycholic acid (UDCA)-peroxidase conjugate as tracer, detected by enhanced chemiluminescence employing a portable charge-coupled device (CCD)-based device. The test was validated in 24 healthy subjects before and after treatment with Loperamide, a drug that increases OITT. The developed CL-EIA was accurate and precise, with a LLOQ of 50pmolL−1. The measured OITT for healthy subjects (291±50min) was fairly well correlated with OITT values obtained by measuring TUDCA in serum (r=0.89). An increased OITT was observed in all the studied subjects after Loperamide treatment. The CL immunosensor can be employed directly in gastroenterology and paediatric units and it can thus represent a new non-invasive simple test for OITT evaluation in a point-of-care setting, with improved diagnostic utility.